HPTLC finger printing profile and evaluation of in vitro antidiabetic potential of medicinally important plant Cassia obtusa L. (Caesalpiniaceae) - K. Thenmozhi, S. Jamuna, K. Karthika, S. Manian, S. Paulsamy, C. Chitravadivu (Journal of Applied Pharmaceutical Science, 2015)
The aim of the study was to establish the finger printing profile and evaluation of in vitro antidiabetic potential of C. obtusa. In vitro antidiabetic activity was carried out according to the method adopted by Miller, 1959. HPTLC studies were carried out using CAMAG HPTLC system equipped with Linomat 5 applicator, TLC scanner 3 and Win cats-4 software for the active fractionation of aqueous-methanolic leaf extracts of C. obtusa. Among the various plant parts analyzed, leaf exhibited efficient inhibitory activity against α-amylase and α-glucosidase enzymes. Therefore, the leaf extract was further fractionated using various solvent systems petroleum ether, chloroform, ethylacetate, butanol and water and were subjected to in vitro antidiabetic activity. Among the fractions analyzed chloroform fraction exhibited remarkable antidiabetic activity by inhibiting α-amylase and α-glucosidase enzymes. Furthermore, the active leaf fractions were analyzed with HPTLC to develop fingerprint profiles and these fractions revealed the presence of 13 and 22 major spots of alkaloids and flavonoids respectively with different Rf values. The results of the present study thus claim the folkloric usage of the plant in diabetic related maladies.
Keywords: Cassia obtusa,antidiabetic activity,HPTLC fingerprint profile,alkaloids,flavonoids.